2022
DOI: 10.3390/ijerph19052509
|View full text |Cite
|
Sign up to set email alerts
|

Post-Migration Stressors and Health-Related Quality of Life in Refugees from Syria Resettled in Sweden

Abstract: The link between post-migration stressors and mental ill health is well documented in refugees resettled in high-income host countries, but the consequences of these stressors on refugees’ health-related quality of life (HRQoL) are less known. This study examined the association between post-migration stressors and HRQoL among Syrian adult refugees resettled in Sweden using a preference-based value set obtained from the general Swedish population. A total of 1215 Syrian adults, ages 18–64 years, granted reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Also, in a study conducted by Matilda Sengoelge et al in Sweden on post-migration stressors and health-related quality of life in Syrian refugees, there was substantial evidence for a negative dose-response relationship (in both unadjusted and modi ed models) with post-migration stress, i.e. nancial and social stress (14). On the other hand, in the research done so far, no study has investigated the quality of life, health, and welfare of Afghans living in refugee camps in the country.…”
Section: Refugeesmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, in a study conducted by Matilda Sengoelge et al in Sweden on post-migration stressors and health-related quality of life in Syrian refugees, there was substantial evidence for a negative dose-response relationship (in both unadjusted and modi ed models) with post-migration stress, i.e. nancial and social stress (14). On the other hand, in the research done so far, no study has investigated the quality of life, health, and welfare of Afghans living in refugee camps in the country.…”
Section: Refugeesmentioning
confidence: 98%
“…On the other hand, in the research done so far, no study has investigated the quality of life, health, and welfare of Afghans living in refugee camps in the country. However, previous studies have shown that the services provided to foreign nationalities is not acceptable (14). This issue requires more attention of the o cials to be paid to the importance of the issue and proper planning to provide services in education, health, and livelihood.…”
Section: Refugeesmentioning
confidence: 99%
“…Having experienced the traumas of war, refugees have to face new stressors connected with being a minority in a foreign country that include learning a foreign language and new social and cultural norms [ 21 ], family-related problems (i.e., being separated from the family and conflicts with relatives), and financial or housing problems or unemployment. It was shown that the stressors related to relocation derive from experiences that are detrimental to mental health, leading in particular to post-traumatic stress disorder (PTSD), anxiety, and depression [ 23 ]. Therefore, such a challenging task such as helping refugees to fully participate in and to contribute to the society should engage authorities at all levels (central, regional, and local) as well as many other entities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, no association was found between the years since immigration to Germany, German citizenship, and HrQoL ( 13 ). A recent study on post-migration stressors and HrQoL among Syrian refugees in Sweden found negative associations between financial and social stress and HrQoL ( 16 ). Furthermore, possible associations between HrQoL, competency stress, and discrimination were identified.…”
Section: Introductionmentioning
confidence: 99%